EFECTO DE DOS PROTECTORES UV EN EL COMPLEJO ESPORA-CRISTAL DE Bacillus thuringiensis subsp. israelensis MICROENCAPSULADO, SOBRE LA ACTIVIDAD LARVICIDA EN Aedes aegypti. - Torres Chiclayo, Keyla Mirely (2017)
The present research aimed to evaluate the photoprotective effect of Zea mays L. "purple maize" and Theobroma cacao L. "cacao" in the spore-crystal complex of Bacillus thuringiensis subsp. israelensis microencapsulated in calcium alginate. Three formulations of Bacillus thuringiensis subsp. israelensis, two with Zea mays L. "purple maize" and Theobroma cacao L. 0.1% "cocoa" and one without UV photoprotector added and they were put in plastic containers of 1 liter capacity, which were filled with 500 mL of distilled water, all treatments were performed in triplicate and exposed to UV radiation from direct solar radiation during days 12 to 17 of July 2017. At 0, 24, 48, 72, 96 and 120 hours of 25 larvae of Ae. aegypti in stage III to each of the treatments and mortality was recorded at 24 hours. The results show significant effects on the wide comparisons of all formulations except for the comparison of Bacillus thuringiensis subsp. israelensis microencapsulated in calcium alginate plus Theobroma cacao L. "cacao" and Bacillus thuringiensis subsp. israelensis microencapsulated in calcium alginate without UV photoprotector added; and a higher percentage of mortality of Aedes aegypti in the formulation Zea mays L. "purple maize" as UV photoprotector, which shows that Zea mays L. "purple maize" presents a better photoprotective action in the spore-crystal complex of Bacillus thuringiensis subsp. israelensis.